Changing strategies of female foeticide in India: a never ending story - Bhattacharya, Sudip; Singh, Amarjeet (International Journal Of Community Medicine And Public Health, 2016)
Once a young lady, walked in the OPD with history of bleeding per vagina for last 24 hours. It was a case of retained products of conception subsequent to induced incomplete abortion. Later we came to know that a team of local private doctors with portable ultrasound machine and MTP kits used to come in the study areas at night hours. This mobile team offered a package deal to the clients. Part one was sex determination test. When a female fetus was detected they offered to do induce abortions (on the spot). This is done in a clandestine way. The team used to leave after initiating the procedure. For any complication they were advised to go to hospital OPD presenting as P/V bleeding to avoid punishment under Pre-Conception and Pre-Natal Diagnostic Techniques (PCPNDT) Act, 1994. As we know every action has an opposite reaction. To prevent female feticides government enacted PNDT Act as an action. Reaction to this people started prenatal sex selection. Again the governmental action was amendment of Pre-Natal Diagnostic Techniques (Regulation and Prevention of misuse) (PNDT) Act, 1994 to PC-PNDT ACT. People's reaction was sex selection in a static van. Due to raids it was converted to mobile van. In our case study it is seen that, to avoid the PC-PNDT Act, people devised a newer strategy. A strategy for sex determination and female feticide by a mobile team with portable ultrasound machines. Our case study is important because we have just explored the tip of the iceberg only. A lot of efforts should be done. Until and unless the people understand the value of women in the society, this kind of reaction will take place again and again.